THE COUNTRY RISK REFLECTED IN THE CDS QUOTATIONS - Mădălina Antoaneta RĂDOI; Alexandru OLTEANU (Challenges of the Knowledge Society)
We know the fact that, with the rapid growth of the economic, political and financial instability, country risk analysis has gained an increasingly important role in the practice of international financial institutions. There have been developed a number of country risk assessment models used by companies that are looking to penetrate new foreign markets or who want to protect and minimize their investment losses, including macro-financial models, econometric models, models developed by the Standard & Poor's and Moody’s rating agencies etc. However, one of the indicators that measure the perception of a country among investors is the CDS (Credit Default Swap) price. By using this tool, an investor will be compensated if the debtor goes bankrupt and as such the lower the CDS price is, the lower the perception of that debtor’s bankruptcy risk is. The purpose of this article is to present the impact of the increase or decrease of CDS quotations on a country's loan costs.